ABBY: A phase 2 randomized trial of crenezumab in mild to moderate Alzheimer disease. (22nd May 2018) - Cummings, Jeffrey L.; Cohen, Sharon; van Dyck, Christopher H.; Brody, Mark; Curtis, Craig; Cho, William; Ward, Michael; Friesenhahn, Michel; Rabe, Christina; Brunstein, Flavia; Quartino, Angelica; Honigberg, Lee A.; et al.
Abstract : Objective: To evaluate the safety and efficacy of crenezumab in patients with mild to moderate Alzheimer disease (AD). Methods: In this phase 2 trial, 431 patients with mild to moderate AD 50 to 80 years of age were randomized 2:1 (crenezumab:placebo). Patients received low-dose subcutaneous crenezumab 300 mg or placebo every 2 weeks (n = 184) or high-dose intravenous crenezumab 15 mg/kg or placebo every 4 weeks (n = 247) for 68 weeks. Primary outcome measures were change in Alzheimer's Disease Assessment Scale–Cognitive Subscale (ADAS-Cog12) and Clinical Dementia Rating–Sum of Boxes scores from baseline to week 73. Results: The primary and secondary endpoints were not met. In an exploratory post hoc analysis, a reduction in decline on the ADAS-Cog12 was observed in the high-dose group. Separation from the placebo group on the ADAS-Cog12 was greatest in the milder subsets of AD patients and reached statistical significance in the group with Mini-Mental State Examination scores of 22 to 26. In both groups, there was a significant increase in CSF β-amyloid1-42 levels that correlated with crenezumab CSF levels. The overall rate of adverse events was balanced between groups. One case of amyloid-related imaging abnormalities indicative of vasogenic edema or effusions was reported. Conclusions: Although prespecified criteria for testing treatment effects were not met, these data suggest a potential treatment effect in patients with mild AD treated with high-dose crenezumab. Together with the safety profile for crenezumab, these data support the exploration of crenezumab treatment at even higher doses in patients with early AD. Clinicaltrials.gov identifier: NCT 01343966. Classification of evidence: This study provides Class II evidence that, for people with AD, crenezumab does not significantly improve cognition or function at 18 months. The study is rated Class II because <80% of enrolled patients completed the study.